The Role of Basin Geometry in Mountain Snowpack Responses to Climate Change - Shea, Joseph M.; Whitfield, Paul H.; Fang, Xing; Pomeroy, John W. (Frontiers in Water, 2021)
Snowmelt contributions to streamflow in mountain basins dominate other runoff sources both annually and seasonally. Increased temperatures and changes in precipitation of future climates will affect both snow accumulation and seasonal runoff timing and magnitude, but the underlying and fundamental roles of mountain basin geometry and hypsometry on snowmelt sensitivity have received little attention. To investigate the role of basin geometry in snowmelt sensitivity, a linear snow accumulation model and the energy-budget snowmelt model built in the Cold Regions Hydrological Modelling platform (CRHM) are used to estimate how hypsometry affects basin-wide snow volumes and snowmelt runoff. Prescribed changes in air temperature alter both the snow accumulation gradient and the total snowmelt energy, leading to snowpack volume reductions (10-40%), earlier melt onsets (1 week to 4 weeks) and end of melt season (3 weeks), increases in early spring melt rates and reductions in seasonal areal melt rates (up to 50%). Basin hypsometry controls the magnitude of the basin response. The most sensitive basins are those with the greatest proportional area at low elevations. The least sensitive basins are those that have the greatest proportional area at high elevations. Basins with similar proportional areas at high and low elevations fall in between the others in terms of sensitivity and other metrics. This work provides context for anticipating the impacts of ongoing hydrological change due to climate change, and provides guidance for both monitoring networks and distributed modelling efforts.